M4 Pseudomonas aeruginosa inhibits aspergillus fumigatus in vitro through multiple mechanisms, including pyoverdine production. (12th November 2019) - Hughes, DA; Armstrong-James, D; Elborn, JS; Davies, JC
Abstract : Objectives: Pseudomonas aeruginosa ( Pa ) and Aspergillus fumigatus ( Af ) are the commonest bacterial and fungal pathogens in CF airways. In vitro studies suggest a complex co-inhibitory interaction between the organisms, with the fluorescent Pa siderophore, pyoverdine, central to this mechanism. We hypothesised that this would be strain-dependent and aimed to explore this further in 2 co-infection models. Methods: 21 clinical Pa isolates from CF patients were selected from our bacterial repository in addition to lab strains ( PA01, PA14 ), and PA14NR transposon mutants lacking pyoverdine ( pvdD, pvdF ) and pyocyanin ( phzM, phzS ). An Af lab strain ( Af293 ) and clinical Af isolate were used. 10 CF Burkholderia cenocepacia ( Bc ) and Staphylococcus aureus ( Sa ) isolates were selected. An Af lawn was generated by suspending 3.3 × 10 5 conidia/ml in 0.5% LB agar, onto which 10 µl of 16 hr bacterial broths were spotted. 72 hr co-cultures (37°C) were imaged at 24 hr intervals in lab (clearance zone estimation) and UV light (semi-quantitative measure of fluorescence). A 96-well plate co-culture model using sterile Pa culture filtrates (PCF) and anti-fungal drugs (Posaconazole, Amphotericin B) above Af cultures quantified this interaction effect using the metabolic Resazurin assay. Results: Pa lab strains and some clinical Pa isolates produced clear zones of Af inhibition, whilst others produced none. Af clearance was linked to strong UV fluorescence (high pyoverdine production) although not exclusively as pvdD inhibited Af growth. No Sa inhibited Af growth but some Bc isolates did. Indirect Af inhibition was quantified and confirmed using lab strain PCFs in 96-well plates. Established Af was less susceptible to anti-fungals and PCF than was early conidial growth. Conclusion: Pa isolates inhibit Af growth, both in direct co-culture and indirectly in a strain-dependent manner; pyoverdine is important but not exclusively so. Further genetic mutants are being used to explore these mechanisms.